Filosofía, educación matemática y ciencias (2021)
Talking about mathematics education is no longer a novelty when we think about the work of the mathematics educator, and even more so when we analyse thatthis work is as old as educational action, and as old as the teaching of mathematics. What automatically links this concept to the history of mathematics, andconsequently to the epistemological work that philosophy has been developing alongside mathematics. The aim of this paper is to describe how this relationshipis presented in the history of mathematics, philosophy and educational work. In order to develop this idea, we will use a qualitative perspective presented in thehistory of mathematical thought as recorded in the texts, to try to determine what is understood today by mathematics education and how it is treated by the workof the mathematics educator in the triple relationship that we have proposed as a title.